2007
DOI: 10.1007/s11102-007-0019-9
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic growth hormone-releasing hormone secretion by a metastatic bronchial carcinoid tumor: a case with a non hypophysial intracranial tumor that shrank during long acting octreotide treatment

Abstract: Ectopic acromegaly represents less than 1% of the reported cases of acromegaly. Although clinical improvement is common after treatment with somatostatin (SMS) analogs, the biochemical response and tumor size of the growth hormone-releasing hormone (GHRH)-producing tumor and its metastases are less predictable. Subject A 36-year-old male was referred because of a 3-year history of acromegaly related symptoms. He had undergone lung surgery in 1987 for a "benign" carcinoid tumor. Endocrine evaluation confirmed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Long-acting somatostatin analogues (octreotide or lanreotide) can represent a first-line therapy, since they may control the endocrine hypersecretion and tumour proliferation, but experience is still limited [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-acting somatostatin analogues (octreotide or lanreotide) can represent a first-line therapy, since they may control the endocrine hypersecretion and tumour proliferation, but experience is still limited [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…About 50 cases of ectopic GHRH-dependent acromegaly have been so far described in the literature [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, only 74 published cases were identified and except for a recent French series of 21 cases most were case reports . Tumours secreting GHRH are mainly NETs, usually welldifferentiated and of pancreatic or bronchial origin accounting for approximately 2/3 of cases (Fainstein et al 2007, Butler et al 2012, Lock et al 2014. The clinical presentation is variable with features similar to those caused from a somatotroph adenoma.…”
Section: Acromegalymentioning
confidence: 99%
“…Hypothalamic tumours, including hamartomas, choristomas, gliomas and gangliocytomas, may also produce excessive GHRH resulting in acromegaly (Di Lorgi et al 2007). Ectopic secretion of GH has only been described in single cases (Melmed et al 2006, Fainstein et al 2007 and represents approximately 0.1% 24:6 of paraneoplastic acromegaly cases (Melmed et al 2006, Fainstein et al 2007). …”
Section: Acromegalymentioning
confidence: 99%
“…In most cases in the literature, the preliminary diagnosis was pituitary acromegaly and diagnosis of ectopic acromegaly was confirmed either during the diagnostic work up or after unsuccessful pituitary surgery. There was a delay of 2 to 18 years between pituitary surgery and establishment of correct diagnosis [29, 45, 66]. Most patients had pituitary hyperplasia visible on imaging with some characteristics indistinguishable from pituitary adenomas, leading often to unnecessary transsphenoidal surgery (TSS) [14, 21, 22, 28, 29, 34, 3941, 43, 44, 51, 53, 56, 62, 63, 66, 67, 69, 70, 74, 78, 79, 81, 94, 95].…”
Section: Diagnostic Evaluation Of Ectopic Acromegalymentioning
confidence: 99%